Inside-Out: Driving Down Direct Air Capture Costs With High-Efficiency Adsorbents - Husk, Jason C.; Wenz, Graham B. (Frontiers in Climate, 2022)
As carbon emissions continue to grow, removing carbon dioxide (CO2) from the atmosphere will be necessary to curb the impact of climate change, with the need to remove over a billion of tonnes of CO2 in the next decade. Direct air capture (DAC) is a promising technology for removing atmospheric carbon dioxide, with a handful of systems deployed around the globe. As currently deployed, however, tens of millions of these systems are needed to address current and historic emissions, which means creating an industry the size of the auto industry – along with consuming the associated resources – within the next decade. Improving DAC processes via scale is not enough; focusing on breakthroughs in sorbent performance is needed to reduce the number of systems and sheer volume of resources needed to rapidly bring DAC to the scales required to prevent further climate change. There are roles for government, corporations, and the carbon removal industry to play in enabling infrastructure, increasing demand, and creating clarity to accelerate deployment of DAC and, more broadly, carbon dioxide removal technologies.